Subject-Spatial and Physical Urban Environment as a Condition for the Psychological Security of Urban Residents - Olga Yu. Zotova (Peoples' Friendship University of Russia (RUDN University), 2023)
Urban residents make up more than half of the world's population. They are the main resource of any modern city or town, and focus on them and their involvement are decisive factors in any successful urbanistic transformation. The purpose of the study is to summarize research in the field of environmental psychology aimed at identifying the conditions for creating psychological security for urban residents. The author made an analysis of more than 385 articles in Russian and English available in the national bibliographic database of scientific publications (Russian Science Citation Index), scientific publishing houses (Elsevier, SprigerLink, SAGE Publishing), publishing houses of open-access scientific journals (MDPI, Frontiers Media), and free digital repository of open-access full-text scientific articles (PubMed Central). Most of them dated back to the last twenty years. Of these, 80 were selected for an analysis. The facts under consideration were systematized in two aspects: objective security conditions associated with the physical environment (visual complexity, soundscape, climate, etc.) and subjective security conditions associated with the peculiarities of their perception by urban residents. To visualize the obtained conditions of the psychological security of urban residents and create an image of a safe city, the Midjourney neural network was used, which makes it possible to generate text-based images. As a result of the analysis of studies of the psychological safety of urban life, it became possible to describe the conditions that form the feeling of psychological security among urban residents; using the Midjourney neural network, to visualize the image of a safe city; to show the role of the soundscape, ordered environment, social control, segmentation of habitable space and its connection with nature; and to justify to some extent the interchangeability of security components.